Information literacy in scientific communication: the experience of PROPETIPS – UNESP - Guimarães, José Augusto Chaves [UNESP]; Hayashi, Maria Cristina Piumbato Innocentini; Rego-Piva, Laura Maria [UNESP] (Biblioteca Central da UNB, 2025)
Created in 2017, by the Vice-Presidency of Research at Unesp, the Propetips series emerges as a pioneering initiative aimed at disseminating information about scientific communication strategies. Aimed at researchers, both teachers and students, these directives provide quick and timely information on scientific communication strategies and aim to increase the visibility of scientific production and raise the academic prestige of the institution. Thus, the objectives are to describe and analyze the experience of information literacy in scientific communication promoted by this series, highlighting its implementation in public and open access spaces. The relevance of this study lies in the growing need for effective strategies that promote the ability to locate, evaluate and use scientific information efficiently, especially in an academic scenario increasingly saturated with information. In methodological terms, a qualitative approach is adopted, focusing on the content analysis of the 42 Propetips made available until 2024. The analysis is structured around the thematic categorization of Propetips classified into a) structural aspects of scientific production and communication; b) ethical aspects; c) strategic aspects; d) visibility and scientific metrics; e) research funding; and f) academic praxis. This is combined with investigation into the presence and prominence of these Propetips on the websites of libraries and postgraduate programs at Unesp and other institutions, to evaluate the capillarity of this initiative and verify its integration into the practices and informational resources offered to researchers. by these academic and library service units. The results point to the effectiveness of Propetips as a training mechanism in scientific communication, emphasizing the importance of its didactic and accessible approach, especially for young researchers and new teachers. The highly significant return that the Propetips publicity had among the 353 new teachers from different areas of knowledge hired by the university in 2023 stands out, attesting to the pertinence, relevance and usefulness of the Propetips contents presented in a simple, didactic and enlightening way, important elements for those who enter an academic career and have scientific practice in their daily lives. It is concluded that Propetips are an important institutional initiative of information literacy in scientific production and communication that provides a culture of knowledge socialization in which the subjects of the process are motivated to disseminate and share these strategic contents with fellow teachers and students, which generates a chain action of high potential.
Alfabetización informacional en comunicación científica: la experiencia del PROPETIPS – UNESP
Alfabetização informacional em comunicação científica: a experiência das PROPETIPS – UNESP
Keywords: Information literacy; Research ethics; Scientific communication